Problem solving and structured programming in Pascal - Koffman, Elliot B. (Massachusetts : Addision-Wesley Publishing Company, 1985)
This text can be used in any introductory programming course that emphasizes a careful, disciplines approach to programming in Pascal.
1. Introduction to computers -- 2. Problem solving -- 3. Control statements -- 4. Simple data types -- 5. More control statements -- 6. Arrays -- 7. Records -- 8. Sets and files -- 9. Recursion, Searching and sorting -- 10. Pointer variables and dynamic data structures.
Includes bibliographical references and index.
Keywords: PASCAL (COMPUTER PROGRAM LANGUAGE)